Multilayer Oil-in-Water Emulsions: Formation, Characteristics and Application as the Carriers for Lipophilic Bioactive Food Components – a Review - Bortnowska Grażyna (Polish Journal of Food and Nutrition Sciences)
This review article demonstrates fundamentals regarding the manufacturing of multilayer oil-in-water (M-O/W) emulsions and factors affecting stability of these systems. Moreover, characteristics of major bioactive lipophilic components and ingredients mostly applied to form multilayered membranes as well analytical methods used to examine properties of M-O/W emulsions are specified. It has been shown that production of M-O/W systems is based on the layer-by-layer (LbL) electrostatic deposition technique which makes use of the electrostatic attraction of oppositely charged surfactants and biopolymers to form multicomposite protective layers around emulsion droplets. Finally, limitations regarding studies of M-O/W systems which should be developed are specified.